(untitled) - FAO (Rome, Italy, 1999)
The book is a compilation of statistical data on basic food and agricultural products for all countries and territories of the world. It primarily includes commodity trade tables (imports and exports, quantity and values) for the year 1996 - 1998 and aggregate value tables for the years 1993 - 1998.
Keywords: agriculture,farm produce,farm trade; statistics